Parents’ knowledge, attitudes and practices regarding household injury of children under 5 years old - CAZACU-STRATU, Angela; COCIU, Svetlana; PLAMADEALA, Alexandru; COMAN, Madalina (One Health & Risk Management, 2023)
Introduction. Around 950,000 children and teenagers die each year as a result of injuries and violence throughout the world. The most common cause of death for children under the age of five is trauma that occurs in the home environment. Aim of the study: To assess the knowledge, attitudes and practices of parents with children aged 0-5 years old regarding unintentional injuries among home environment. Materials and methods. Parents of children under five years old were asked to complete a survey between October and December 2021, which was distributed online via social media. The questionnaire contained 43 items and was analysed using Microsoft Excel. Results. The questionnaire was completed by 300 parents with children up to 5 years old, mostly aged between 26-35 years old (72%), with high education (79.3%), of them 96% females, majority from urban areas (79.7%), with medium socio-economic status. Nearly 75% of respondents believe their child could get hurt at home, most commonly through an injury (42.7%), followed by ingesting foreign objects (22%). Falls were the primary cause of the majority of the child’s accidents over the last year (60%) despite them being uncommon (54.7%) and infrequent (22%) in nature. Most often (54.7%), parents said that they see and hear their child all the time, but occasionally leave them for a short time. When their child suffered an injury at home, only 33.3% of parents sought medical attention. Conclusion. The results of this study will allow for a greater focus on young children’s safety in the household. By identifying and emphasizing the knowledge, attitudes, and practices of parents with children 0–5 years old, we will be able to notify the necessary authorities and advise particular measures to prevent home accidents.